Synthesis of 3,5-Diaryl-4-benzoyl-1-pyridoyl Pyrazoles by Oxidation of Pyrazolines using DMSO-I2 Solvent - KADU, M.V.; KHADSAN, R.E.; JAMODE, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl-4-benzoyl-1-pyridoyl pyrazoles have been synthesized by the oxidation of pyrazolines, by using I2 in DMSO solvent. The structures of these compounds have been established by spectral analysis (IR, NMR and UV) and elemental analysis.